Detecting backdoor using stepping stone detection approach - Alminshid, Khalid; Omar, Mohd Nizam (2013)
Several techniques are used by intruders to hide the track of intrusion in the network.One of these techniques executes by using series of hosts in network (stepping stones chain), which can be detected by using an approach, called Stepping Stone Detection (SSD). However, during all previous years, SSD was only confined to detect this type of intrusion.This paper discusses the using of SSD approach and potential applications in other emerging field by introduce the using of SSD concepts in backdoor attack detection field.This research shows that by using SSD to detect backdoor attack can be gained very low false negative and false positive rates and reduces the scan process time detection.